Enhanced Rho‐Associated Protein Kinase Activation in Patients With Systemic Lupus Erythematosus. Issue 6 (30th May 2013) - Isgro, Josephine; Gupta, Sanjay; Jacek, Elzbieta; Pavri, Tanya; Duculan, Roland; Kim, Mimi; Kirou, Kyriakos A.; Salmon, Jane E.; Pernis, Alessandra B.
Abstract : Objective: Rho‐associated protein kinases (ROCKs) have been implicated in the pathogenesis of cardiovascular and renal disorders. We recently showed that ROCKs could regulate the differentiation of murine Th17 cells and the production of interleukin‐17 (IL‐17) and IL‐21, two cytokines associated with systemic lupus erythematosus (SLE). The goal of this study was to assess ROCK activation in human Th17 cells and to evaluate ROCK activity in SLE patients. Methods: An enzyme‐linked immunosorbent assay (ELISA)–based ROCK activity assay was used to evaluate ROCK activity in human cord blood CD4+ T cells differentiated under Th0 or Th17 conditions. We then performed a cross‐sectional analysis of 28 SLE patients and 25 healthy matched controls. ROCK activity in peripheral blood mononuclear cell (PBMC) lysates was determined by ELISA. Cytokine and chemokine profiles were analyzed by ELISA. Results: Human cord blood CD4+ T cells differentiated under Th17 conditions expressed higher levels of ROCK activity than did CD4+ T cells stimulated under Th0 conditions. Production of IL‐17 and IL‐21 was inhibited by the addition of a ROCK inhibitor. SLE PBMCs expressed significantly higher levels of ROCK activity than did healthy control PBMCs (1.25 versus 0.56; P = 0.0015). Sixteen SLE patients (57%) expressed high levels of ROCK (optical density at 450 nm >1). Disease duration, lymphocyte count, and azathioprine use were shown to be significant independent predictors of ROCK activity in multivariable analyses. Conclusion: Consistent with previous results in the murine system, increased ROCK activation was associated with Th17 cell differentiation. Moreover, enhanced ROCK activity was observed in a subgroup of SLE patients. These data support the concept that the ROCK pathway could represent an important therapeutic target for SLE.